2019
DOI: 10.1093/dote/doz071
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes of robot-assisted minimally invasive versus open esophagectomy in patients with esophageal squamous cell carcinoma: a propensity score-weighted analysis

Abstract: SUMMARY Robots are increasingly used in minimally invasive surgery. We evaluated the clinical benefits of robot-assisted minimally invasive esophagectomy (RAMIE) in comparison with the conventional open esophageal surgery. From 2012 to 2016, 371 patients with esophageal squamous cell carcinoma underwent an Ivor Lewis or McKeown procedure at our institution. Of these, 130 patients underwent laparoscopic gastric conduit formation followed by RAMIE, whereas 241 patients underwent conventional esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 21 publications
1
62
0
1
Order By: Relevance
“…If minimally invasive thoracoscopy is superior to thoracotomy in the context of esophagectomy, is still a matter of debate [23,25,27,29,30]. However, ample evidence including the prospectively conducted randomized MIRO trial reported considerably higher incidences of major pulmonary complications after open esophagectomy (OE) compared to hybrid minimally invasive laparoscopically assisted esophagectomy (LAE) [21,22,24,[29][30][31][32]. This might be due to reduced abdominal pain and trauma in comparison to open surgery [15,[17][18][19][20]22,31,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…If minimally invasive thoracoscopy is superior to thoracotomy in the context of esophagectomy, is still a matter of debate [23,25,27,29,30]. However, ample evidence including the prospectively conducted randomized MIRO trial reported considerably higher incidences of major pulmonary complications after open esophagectomy (OE) compared to hybrid minimally invasive laparoscopically assisted esophagectomy (LAE) [21,22,24,[29][30][31][32]. This might be due to reduced abdominal pain and trauma in comparison to open surgery [15,[17][18][19][20]22,31,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, ample evidence including the prospectively conducted randomized MIRO trial reported considerably higher incidences of major pulmonary complications after open esophagectomy (OE) compared to hybrid minimally invasive laparoscopically assisted esophagectomy (LAE) [21,22,24,[29][30][31][32]. This might be due to reduced abdominal pain and trauma in comparison to open surgery [15,[17][18][19][20]22,31,[33][34][35]. As the trauma-associated release of danger-associated molecular patterns (DAMPs) is expected to directly cause pulmonary barrier dysfunction [17,19,20], a better early postoperative lung function should be expected in patients undergoing minimally invasive surgery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lewis). Neben der im Folgenden vorgestellten Technik sind von anderen Arbeitsgruppen unterschiedliche technische Vorgehensweisen publiziert worden [5,6]. Aus unserer Sicht kann die roboterassistierte Operation, insbesondere beim thorakalen Teil mit Anastomose und Lymphadenektomie, die technischen Limitationen der konventionellen thorakoskopischen Technik überwinden.…”
Section: Introductionunclassified